2012
DOI: 10.1029/2011ja017365
|View full text |Cite
|
Sign up to set email alerts
|

The true fluence distribution of terrestrial gamma flashes at satellite altitude

Abstract: [1] In this paper we use the fluence distributions observed by two different instruments, RHESSI and Fermi GBM, corrected for the effects of their different orbits, combined with their different daily TGF detection rates and their relative sensitivities to make an estimate of the true fluence distribution of TGFs as measured at satellite altitudes. The estimate is then used to calculate the dead-time loss for an average TGF measured by RHESSI. An independent estimate of RHESSI dead-time loss and true fluence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 35 publications
10
96
2
1
Order By: Relevance
“…Although the distribution in Figure 9 is quite similar to what was found by Østgaard et al [2012] and Tierney et al [2013], a direct comparison cannot be made for the following reasons: The TGFs used in Østgaard et al [2012] are only the TGFs observed by RHESSI before the degradation of the instrument in 2005–2006, while we use the TGFs measurements made up until to 2011. As the strong TGFs from after 2005 are mixed with the weaker TGFs from before 2005, this causes a softer distribution which becomes apparent when using all our TGFs.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Although the distribution in Figure 9 is quite similar to what was found by Østgaard et al [2012] and Tierney et al [2013], a direct comparison cannot be made for the following reasons: The TGFs used in Østgaard et al [2012] are only the TGFs observed by RHESSI before the degradation of the instrument in 2005–2006, while we use the TGFs measurements made up until to 2011. As the strong TGFs from after 2005 are mixed with the weaker TGFs from before 2005, this causes a softer distribution which becomes apparent when using all our TGFs.…”
Section: Resultssupporting
confidence: 51%
“…The figure shows that a relatively larger number of the second catalog TGFs originates from distances between 400 and 500 km from satellite foot point than the TGFs in the first catalog. The catalog 2 TGFs that are seen to come from close distances might either be in the lower end of a power law distribution as indicated by Østgaard et al [2012] or be equally strong TGFs originating from further below the tropopause.…”
Section: Resultsmentioning
confidence: 87%
“…En effet, on estime que les TGF produits sur l'ensemble de la planète et potentiellement détectables par l'instrument Gamma ray Burst Monitor (GBM) à bord de Fermi, sont au nombre de 400 000 par an [14]. Il s'agit là d'un minimum car les instruments opération-nels actuellement ne sont pas optimisés pour la détection des TGF, et il n'est pas impossible qu'en fait, tous les éclairs intranuages produisent des TGF [15]. Dans ce contexte, il est intéressant de noter qu'on estime que 30 éclairs intranuages se déclenchent par seconde à la surface du globe, soit environ 3 millions par jour.…”
Section: Caractéristiques Des Tgfunclassified
“…2a. As indicated in Ostgaard et al (2012), RHESSI has an effective area for detecting TGF σ TGF R of about 256 cm 2 . The Astro-Rivelatore Gamma a Immagini Leggero (AG-ILE) is a satellite from the Italian Space Agency dedicated to the study of high-energy gamma rays (typically above 50 MeV) in the universe.…”
Section: Tgf Detection Performancementioning
confidence: 99%
“…Gjesteland et al (2012) indicate that n min R = 11 (for the RHESSI second catalogue) and Ostgaard et al (2012) radial distance between the TGF source (projection at satellite altitude) and the satellite for photons (various altitudes) and electrons (seen at the hemisphere of production and in the opposed hemisphere). The two electron profiles correspond to a detection altitude of 560 km, but are very close for 490 or 700 km altitude.…”
Section: Estimating Tgf and Teb Detection Ratesmentioning
confidence: 99%